Effects of naringin on the proliferation and osteogenic differentiation of human amniotic fluid‐derived stem cells. (11th June 2014) - Liu, Meimei; Li, Yan; Yang, Shang‐Tian
Abstract: Human amniotic fluid‐derived stem cells (hAFSCs) are a novel cell source for generating osteogenic cells to treat bone diseases. Effective induction of osteogenic differentiation from hAFSCs is critical to fulfil their therapeutic potential. In this study, naringin, the main active compound of Rhizoma drynariae (a Chinese herbal medicine), was used to stimulate the proliferation and osteogenic differentiation of hAFSCs. The results showed that naringin enhanced the proliferation and alkaline phosphatase activity (ALP) of hAFSCs in a dose‐dependent manner in the range 1–100 µg/ml, while an inhibition effect was observed at 200 µg/ml. Consistently, the calcium content also increased with naringin concentration up to 100 µg/ml. The enhanced osteogenic differentiation of hAFSCs by naringin was further confirmed by the dose‐dependent upregulation of marker genes, including osteopontin ( OPN ) and Collagen I from RT–PCR analysis. The increased osteoprotegerin ( OPG ) expression and minimal expression of receptor activator of nuclear factor‐ κ B ligand ( RANKL ) suggested that naringin also inhibited osteoclastogenesis of hAFSCs. In addition, the gene expressions of bone morphogenetic protein 4 ( BMP4 ), runt‐related transcription factor 2 ( RUNX2 ), β‐catenin and Cyclin D1 also increased significantly, indicating that naringin promotes the osteogenesis of hAFSCs via the BMP and Wnt– β ‐catenin signalling pathways. These results suggested that naringin can be used to upregulate the osteogenic differentiation of hAFSCs, which could provide an attractive and promising treatment for bone disorders. Copyright © 2014 John Wiley & Sons, Ltd.